2014
DOI: 10.1371/journal.pone.0086200
|View full text |Cite
|
Sign up to set email alerts
|

HIV Pre-Exposure Prophylaxis Interest among Female Sex Workers in Guangxi, China

Abstract: ObjectivesAcceptability of pre-exposure prophylaxis (PrEP) and willingness to participate in a clinical trial for both safety and efficacy of PrEP were investigated among female sex workers (FSWs) in Guangxi, China.MethodsA cross-sectional study was performed in three cities in Guangxi. Structured, self-administered questionnaires were used to assess the acceptability of PrEP and the willingness to participate in a clinical trial. Multivariable logistic regression models were fitted to identify predictors.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 55 publications
(92 reference statements)
4
29
0
Order By: Relevance
“…[65, 106, 108] Once the concept of PrEP was introduced, female sex workers across the world expressed strong interest in using PrEP across seven studies (N = 4809 total participants) [18, 24, 46, 65, 68, 106, 108]. Interest rose across these studies over time, in the range of 61–69% in 2010 –2012 [18, 65, 68, 108] up to 86% in 2014 [106]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[65, 106, 108] Once the concept of PrEP was introduced, female sex workers across the world expressed strong interest in using PrEP across seven studies (N = 4809 total participants) [18, 24, 46, 65, 68, 106, 108]. Interest rose across these studies over time, in the range of 61–69% in 2010 –2012 [18, 65, 68, 108] up to 86% in 2014 [106]. …”
Section: Resultsmentioning
confidence: 99%
“…High alcohol consumption by some sex workers was also a repeated concern [46]. Three Chinese studies found that the higher a sex worker assessed her own HIV risk, the more likely she was to find PrEP acceptable [68, 106, 108]. …”
Section: Resultsmentioning
confidence: 99%
“…To assess willingness to participate in a biomedical study to study PrEP or microbicidal rings in this population, participants were asked, “How willing would you be to provide a self-collected vaginal swab for a research study like this?” and “How willing would you be to provide a blood sample for a research study like this?” Questions were adapted from published studies. 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…This was a particular issue for vaccine or drug trials, but not for observational studies. Safety concerns were mentioned in 45 papers [1, 20-23, 26, 28, 30-32, 34, 36, 37, 39-42, 45, 47, 48, 50-53, 55, 56, 58, 59, 61, 62, 67-69, 71, 76, 77, 88, 92-99], ranked in the top three reasons 32 times [1, 20, 21, 23, 30-32, 36, 37, 40, 41, 45, 47, 48, 50-53, 55, 56, 58, 61, 65, 67-69, 71, 77, 93, 94, 96-98], and identified as the top reason for non-participation 16 times [31,32,40,45,47,48,55,58,61,65,68,71,77,93,94,96,98]. Safety concerns were consistently ranked as most important in all categories, with the exception of North Africa and the Middle East, where they ranked second.…”
Section: Safety Concernsmentioning
confidence: 99%